Finite Element Analysis of Ti-6Al-4V Lattice Cubic Scaffolds for Mandibular Bone Implant Applications - Yasya Khalif Perdana Saleh; Rifky Ismail; Jamari Jamari; I Nyoman Jujur; Suryadi Suryadi; Rochmad Winarso; Tepi Anggara (Advances in Technology Innovation, 2025)
This study evaluates the compressive strength of a cubic lattice scaffold made from Titanium alloy (Ti-6Al-4V) for mandibular bone implants. Scaffold designs with pore sizes ranging from 800 µm to 1000 µm were analyzed using finite element analysis under compressive forces of up to 800 N. Pore sizes of 800 µm and 850 µm achieved a safety factor greater than 1.4, indicating their suitability for both dynamic and static loading. Planned production with bound metal deposition, maintaining a density below 35%, emphasizes material efficiency and cost-effectiveness. Results indicate that 800 µm and 850 µm pore sizes offer optimal strength and safety, suggesting effective mandibular implant integration. Further research on cyclic load testing and osseointegration is recommended.